(untitled) (Balneo and PRM Research Journal, 2024)
Introduction: Hip arthroplasty conducted through either cemented or cementless prostheses must alleviate pain and restore joint mobility and muscle strength. The main goal is to restore mobility, stability and to maintain ADL (Activities of Daily Living) within normal parameters. Current surgical techniques allow for state-of-the-art surgeries to be performed. Yet, the postoperative course is strongly influenced by both pre-and postoperative psychological factors, as well as by associated diseases. Materials and Methods: We present the case of a 79-year-old female patient from Iasi, a retired yet still physically active gym teacher who was admitted an emergency to the Orthopedics Clinic of the ”Sf. Spiridon” Emergency Hospital with a displaced left femoral neck fracture resulting from same-level fall. The patient had for 6 years a Scorpio-Stryker cemented knee prosthesis on the same leg. Through surgical intervention, a cementless bipolar Lépine prosthesis was inserted into the left hip. Then, the patient presented to the Department of Physical Medicine and Rehabilitation of the Iasi Clinical Railroad Hospital to receive an adequate post-operative rehabilitation program. Results: The psychosocial factors have been analyzed with the help of various recent and specialized psychological scales. The obtained results confirm the fact that these factors significantly influence the rehabilitation of prosthesis-wearing patients. Conclusion: Our study emphasizes the psychological impact on standing and walking rehabilitation in a patient with two prostheses on the same motor axis.